Health literacy of hospital patients using a linguistically validated Croatian version of the Newest Vital Sign screening test (NVS-HR) - Brangan, Sanja (PLoS One, 2018)
The Newest Vital Sign (NVS) is a simple, quick and accurate screening test for health literacy (HL). It has been validated for different languages but, to date, not for the Croatian language. The aim of this study was to develop a linguistically validated Croatian version of the NVS and to use it at a later stage in a pilot study of health literacy assessment of hospital patients in Croatia. A full linguistic validation procedure was applied, including forward and backward translation, expert panel review, cognitive interview with 10 respondents from general population, and full involvement in the procedure of one of the screening test developers, the lead author of the NVS-UK version. HL testing on 100 hospital patients (55% women, median age 63.5 years) revealed 58% of patients had less than adequate HL level (scores less than 4), and mean NVS total score was 3.34. A positive significant association was observed between HL and educational level (p = 0.002). A high percentage of patients (92%) did not object to being tested for HL by their primary care physician or in hospital, and 99% of patients would recommend HL testing among patients in general. The respondents' positive views on HL testing and mean completion time of 4 minutes indicate that the Croatian version of the NVS (NVS-HR) could be recommended for use in both clinical and research settings in Croatia.